Photostability of photosynthetic complexes coupled to silver nanowires - Twardowska, Magdalena; Olejnik, Maria; Mackowski, Sebastian (Photonics Letters of Poland, 2013)
We investigate the influence of plasmonic excitations in silver nanowires upon the photostability of photosynthetic complex placed at their vicinity. Strong interaction between the two nanostructures is evident through increase of the fluorescence intensity of the photosynthetic complexes close to the nanowires as compared to uncoupled ones and shortening of the fluorescence lifetime. Analysis of movies collected using a wide-field fluorescence microscope with respect to temporal intensity variations for photosynthetic complexes located along and at the ends of the nanowires, indicate that the photostability is unaffected by the interaction with plasmonic excitations in metallic nanoparticles. Therefore, we conclude that in the case of studied hybrid nanostructures coupling with metallic nanoparticles results in higher number of photons emitted from chlorophyll molecules. Full Text: PDF References R.E. Blankenship, Wiley-Blackwell, ISBN: 978-0-632-04321-7 (2002). Ł. Bujak, N. Czechowski, D. Piatkowski, R. Litvin, S. Mackowski, T.H.P. Brotosudarmo, R.J. Cogdell, S. Pichler, W. Heiss, "Fluorescence enhancement of light-harvesting complex 2 from purple bacteria coupled to spherical gold nanoparticles", Appl. Phys. Lett. 99, 173701 (2011). CrossRef N. Czechowski, P. Nyga, M.K. Schmidt, T.H.P. Brotosudarmo, H. Scheer, D. Piatkowski, S. Mackowski, "Absorption Enhancement in Peridinin–Chlorophyll–Protein Light-Harvesting Complexes Coupled to Semicontinuous Silver Film", Plasmonics 7, 115 (2012). CrossRef J.B. Nieder, R. Bittl, M. Brecht, "Fluorescence Studies into the Effect of Plasmonic Interactions on Protein Function", Angew. Chem. Int. Ed. 49, 10217 (2010). CrossRef A. O. Govorov, I. Carmeli, "Hybrid Structures Composed of Photosynthetic System and Metal Nanoparticles: Plasmon Enhancement Effect", Nano Letters 7, 620 (2007). CrossRef M. Olejnik, B. Krajnik, D. Kowalska, M. Twardowska, N. Czechowski, E. Hofmann, S. Mackowski, "Imaging of fluorescence enhancement in photosynthetic complexes coupled to silver nanowires", Appl. Phys. Lett. 102, 083703/1 (2013). CrossRef P. Anger, P. Bharadwaj, L. Novotny, "Enhancement and Quenching of Single-Molecule Fluorescence", Phys. Rev. Lett. 96, 113002 (2006). CrossRef J.R. Lakowicz, "Radiative Decay Engineering: Biophysical and Biomedical Applications", Analytical Biochemistry 298(1), 1 (2001). CrossRef K. Ray, R. Badugu, J.R. Lakowicz, "Metal-Enhanced Fluorescence from CdTe Nanocrystals: A Single-Molecule Fluorescence Study", J. Am. Chem. Soc. 128, 8998 (2006). CrossRef S. Mackowski, S. Wörmke, A.J. Maier, T.H.P. Brotosudarmo, H. Harutyunyan, A. Hartschuh, A.O. Govorov, H. Scheer, C. Bräuchle, "Metal-Enhanced Fluorescence of Chlorophylls in Single Light-Harvesting Complexes", Nano Letters 8, 558 (2008). CrossRef A.D. Ferguson, E. Hofmann, J. W. Coulton, K. Diederichs, W. Welte, "Siderophore-Mediated Iron Transport: Crystal Structure of FhuA with Bound Lipopolysaccharide", Science 282, 2215 (1998). CrossRef K.E. Korte, S.E. Skrabalak, Y. Xia, "Rapid synthesis of silver nanowires through a CuCl- or CuCl2-mediated polyol process", J. Mater. Chem. 18, 437 (2008). CrossRef T.H.P. Brotosudarmo, E. Hofmann, R.G. Hiller, S. Wörmke, S. Mackowski, A. Zumbusch, C. Bräuchle, H. Scheer, "Peridinin–chlorophyll–protein reconstituted with chlorophyll mixtures: Preparation, bulk and single molecule spectroscopy", FEBS Letters 580, 5257 (2006). CrossRef